An annotated list of the species of lice (Insecta: Phthiraptera) described by Mohammad A.-R. Ansari - Naz, Saima; Najer, Tomas; Gustafsson, Daniel R. (Zootaxa, 2020)
Mohammad Atiq-ur-Rahman Ansari (1911–1979) was an Indian phthirapterist who contributed to the knowledge of parasitic lice (Insecta: Phthiraptera) from the Indian subcontinent with 41 papers published from 1944 to 1968. He described 195 new species and subspecies of chewing lice from birds and redescribed 182 previously known species of all groups of lice. Among the new species, 155 are still considered valid. We list all the species and subspecies described by Ansari under their original binomial or trinomial names, adding for each one: subsequent references by Ansari, current taxonomic status (i.e. taxa placed now in different genera, or with senior synonyms), type host, type locality, and deposition of type material when still extant. About 120 (62%) of Ansari’s primary type specimens are deposited at museums in the United Kingdom and the U.S.A., with the remaining 75 primary types presumed lost. Four species are here considered species inquirenda, because the morphological data published by Ansari are not consistent with diagnostic characters of the genera in which he placed them, and their types could not be located to confirm their correct generic placement. They are Capraiella masumae Ansari, 1955; Craspedorrhynchus chicquera Ansari, 1955; Cuculicola jamilae Ansari, 1955 and Cuculoecus distinctus Ansari, 1955. We propose the name Philopterus ansarii nomen novum as a replacement for Philopterus kalkalichi Ansari, 1956e—preoccupied by Philopterus kalkalichi Ansari, 1955e—and designate a neotype for it. We also designate a neotype for Alcedoecus anularis Ansari, 1955e and Alcedoecus annulatus Tendeiro, 1965a, placing the latter name as an absolute junior synonym of the former.